Antibacterial Activity of Chalcone and Dihydrochalcone Compounds from Uvaria chamae Roots against Multidrug-Resistant Bacteria. (27th August 2018) - Koudokpon, H.; Armstrong, N.; Dougnon, T. V.; Fah, L.; Hounsa, E.; Bankolé, H. S.; Loko, F.; Chabrière, E.; Rolain, J. M.
Abstract : This study presents antimicrobial properties of Uvaria chamae roots, commonly used for the treatment of various infections in south Benin. Their constituents were extracted and then fractionated in order to isolate the active ingredients. Antimicrobial susceptibility tests were performed against several multidrug-resistant bacteria using the Mueller Hilton well agar diffusion method. Results showed that ethanol extracts were highly active against Gram-positive cocci . This activity was more extensive than that measured from conventional broad-spectrum antibiotics. Indeed, vancomycin-resistant enterococcus (VRE) and methicillin-resistant Staphylococcus aureus (MRSA) strains were all sensitive to this root extract. The aim of this study was to link the antimicrobial activity of the root to chemical structures. The ion mobility mass spectrometry analysis revealed for the first time the presence of ten chalcone and dihydrochalcone structures responsible for the antimicrobial activity of Uvaria chamae ethanol extracts. Two structures were described here for the first time in these roots. These findings confirm and justify the medical properties of these roots used as a traditional medicine.